Empowering Local Communities to Help Solve Plastic Waste Through Education and Recycling Solution - Indah Widiastuti; Danar Susilo Wijayanto; Cucuk Wawan Budiyanto; Taufik Wisnu Saputra (FKIP Universitas Sebelas Maret, 2024)
This community service program aims to create awareness of the plastic pollution challenge by empowering the local communities around Sekolah Alam Solo Raya (SELASAR). The program is part of a problem-based learning approach implemented to support community-based education in SELASAR. SELASAR’s students are expected to educate the communities in sorting the general waste and separating out items that can be recycled. The educational kit of a simple recycling machine will be developed in UNS and then installed in Sekolah Alam Solo Raya for educational purposes. The communities will take an educational tour through plastic recycling, from sorting to final production. The objective of the educational tour is to raise awareness of waste reduction and provide practical tips on how to create a more sustainable environment. It is also expected that students could create well-designed products that have more commercial value.